2010
DOI: 10.1074/jbc.m110.107805
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of MRP2/ABCC2 and BSEP/ABCB11 Expression in Sandwich Cultured Human and Rat Hepatocytes Exposed to Inflammatory Cytokines TNF-α, IL-6, and IL-1β

Abstract: In the present study MRP2/ABCC2 and BSEP/ABCB11 expression were investigated in sandwich cultured (SC) human and rat hepatocytes exposed to the proinflammatory cytokines. The investigation was also done in lipopolysaccharide (LPS)-treated rats. In SC human hepatocytes, both absolute protein and mRNA levels of MRP2/ABCC2 were significantly downregulated by TNF-␣, IL-6, or IL-1␤. In contrast to mRNA decrease, which was observed for BSEP/ABCB11, the protein amount was significantly increased by IL-6 or IL-1␤. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 42 publications
2
36
1
Order By: Relevance
“…Discrepant data have been reported in the effects of proinflammatory cytokines on the main canalicular transporters BSEP and MRP2. Thus, transcripts of these two transporters were not affected by LPS in human liver slices (Elferink et al, 2004); by contrast, they were repressed by IL-1b and IL-6 whereas BSEP protein, unlike MRP2, was induced in sandwich-cultured human hepatocytes (Diao et al, 2010). Such discrepancies are likely due to the use of different experimental models and conditions such as cytokine concentrations.…”
Section: Impact Of Inflammation On Chlorpromazine Hepatotoxicity 1563mentioning
confidence: 79%
“…Discrepant data have been reported in the effects of proinflammatory cytokines on the main canalicular transporters BSEP and MRP2. Thus, transcripts of these two transporters were not affected by LPS in human liver slices (Elferink et al, 2004); by contrast, they were repressed by IL-1b and IL-6 whereas BSEP protein, unlike MRP2, was induced in sandwich-cultured human hepatocytes (Diao et al, 2010). Such discrepancies are likely due to the use of different experimental models and conditions such as cytokine concentrations.…”
Section: Impact Of Inflammation On Chlorpromazine Hepatotoxicity 1563mentioning
confidence: 79%
“…In vitro effects of proinflammatory cytokines on the dmd.aspetjournals.org expression of various transporters have also been reported (Petrovic et al, 2007). Three proinflammatory cytokines, IL-6, IL-1, and TNF-a, downregulate hepatic transporter expression in hepatocyte sandwich cultures (Diao et al, 2010). IFN-g and oncostatin M (a member of the IL-6 family) also influenced transporter levels in cultured hepatocytes (Donato et al, 1993;Guillen et al, 1998;Le Vee et al, 2009;Chen et al, 2011).…”
Section: Preclinical Approaches To Cytokine-mediated Tp-ddi Evaluationmentioning
confidence: 99%
“…The bile salt export pump as well as sinusoidal solute carrier uptake transporters are generally suppressed, whereas ATPbinding cassette drug efflux pumps are either unchanged or are up or downregulated depending on the transporter isoform. These changes are observed at mRNA levels for some transporters, and at protein and activity levels for others (Diao et al, 2010). Currently, the clinical relevance of these changes in transporter levels is unclear.…”
Section: Preclinical Approaches To Cytokine-mediated Tp-ddi Evaluationmentioning
confidence: 99%
“…It is to be noted that recent research findings have demonstrated that in addition to drug metabolizing enzyme activities, uptake and efflux transporters also play critical roles in the manifestation of adverse drug effects 10,45 . Human hepatocyte assays for the evaluation of uptake and efflux transporters have been established and are being applied towards drug development [46][47][48][49][50] . These transporter assays, when applied in conjunction with the assays described in this chapter, should aid the selection of the most appropriate drug candidates for further drug development.…”
Section: Resultsmentioning
confidence: 99%